Functionals with extrema at reproducing kernels - Kulikov, Aleksei (Geometric and functional analysis, 2022)
We show that certain monotone functionals on the Hardy spaces and convex functionals on the Bergman spaces are maximized at the normalized reproducing kernels among the functions of norm 1, thus proving the contractivity conjecture of Pavlović and of Brevig, Ortega-Cerdà, Seip and Zhao and the Wehrl-type entropy conjecture for the SU (1, 1) group of Lieb and Solovej, respectively.